Analisis Pengelolaan Keuangan Dalam Rumah Tangga Perspektif Islam (Studi Kasus Pada Ibu Tangga di Kelurahan Sidomulyo Barat Kota Pekanbaru) - Adriani A (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine how financial management in households is based on an Islamic perspective in the West Sidomulyo sub-district. This type of research is qualitative research using interview methods and direct observation of mothers in the West Sidomulyo environment. The results of this study are that mothers in the West Sidomulyo sub-district have managed their finances well, as evidenced by the fact that their expenses are not greater than their income or in the sense that their expenses are not greater than their income. Mothers in the West Sidomulyo sub-district have also recorded their finances, although very simply, although some of them also do not record their finances, only looking at the priority scale: paying Zakat and infaq, Education and daily needs. However, in the concept of managing family finances from an Islamic perspective, they do not fully understand it. It's just that they already believe that Allah SWT's sustenance is given as long as we try and work without giving up and also apply Islamic values. Seeking sustenance in a way that Allah SWT approves. The concept of openness between husband and wife is also part of the Islamic perspective.